2023
DOI: 10.26434/chemrxiv-2023-6q06z-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate and efficient spin-phonon coupling and spin dynamics calculations for molecular solids

Abstract: Molecular materials are poised to play a significant role in the development future opto-electronic and quantum technologies. A crucial aspect of these areas is the role of spin-phonon coupling and how it facilitates energy-transfer processes such as intersystem crossing, quantum decoherence, and magnetic relaxation. Thus, it is of significant interest to be able to accurately calculate molecular spin-phonon coupling and spin dynamics in the condensed phase. Here we examine the various approximations inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…32 However, we have recently shown that there is little impact on the spin dynamics when either fixed, approximated, or calculated linewidths are used, provided the BZ is integrated with a sufficiently dense q-point grid. 33 4 Electronic structure of lanthanide complexes Now we turn to the spin states of the molecule, where herein we focus on the low-lying electronic states of Ln complexes. For most cases, the trivalent Ln 3+ oxidation state is most relevant, with a well-isolated ground configuration 4f n 5s 2 5p 6 ; the 6s and 5d may become relevant depending on the oxidation state and the ligands surrounding the metal.…”
Section: Phononsmentioning
confidence: 99%
See 4 more Smart Citations
“…32 However, we have recently shown that there is little impact on the spin dynamics when either fixed, approximated, or calculated linewidths are used, provided the BZ is integrated with a sufficiently dense q-point grid. 33 4 Electronic structure of lanthanide complexes Now we turn to the spin states of the molecule, where herein we focus on the low-lying electronic states of Ln complexes. For most cases, the trivalent Ln 3+ oxidation state is most relevant, with a well-isolated ground configuration 4f n 5s 2 5p 6 ; the 6s and 5d may become relevant depending on the oxidation state and the ligands surrounding the metal.…”
Section: Phononsmentioning
confidence: 99%
“… 32 However, we have recently shown that there is little impact on the spin dynamics when either fixed, approximated, or calculated linewidths are used, provided the BZ is integrated with a sufficiently dense q -point grid. 33 …”
Section: Phononsmentioning
confidence: 99%
See 3 more Smart Citations